Crises paroxísticas recorrentes em ratos por inibição do transporte de glutamato durante o desenvolvimento - Cattani, Adriano Augusto Giaquinto [UNIFESP] (2009)
It has been previously shown that cell-surface glutamate transporters efficiently control network activity in the maturing rodent brain, preventing the generation of seizures. In particular, inhibition of glutamate transporters by DL-TBOA leads to a pathological EEG pattern in freely moving rat pups. This is composed of partial seizures and recurrent short paroxysmal bursts, alternating with silent periods, and is characteristic of “suppression burst” activity (SB). The association of SB and partial seizures is observed in neonates suffering from early epileptic encephalopathy, raising the possibility that glutamate transporters could be implicated in this syndrome. Interestingly, TBOA produces recurrent long lasting depolarizations and bursts of action potentials in interneurons and pyramidal cells in cortical slices. This pattern referred to as slow network oscillations (SNOs) and the seizures observed in vivo, were blocked by the NMDA receptor antagonist (APV), suggesting that they share similar mechanisms. Therefore, SNOs provide a suitable in vitro model for investigating the mechanisms involved in the genesis of paroxysmal activity. Using electrophysiological recordings we show that SNOs reflect two processes that occur during inhibition of glutamate transporters: (1) An ambient increase in glutamate concentrations, that tonically activates both NMDA receptors and glutamate metabotropic receptors (mGluRs). The activation of mGluRs reduces the potassium current (IM), increasing neuronal excitability. (2) A phasic release of glutamate that spills out of synapses and activates extrasynaptic NMDA receptors located in both interneurons and pyramidal cells. Using multibeam two-photon microscopy, we analyzed SNOs calcium dynamics and show that they are associated with recurrent calcium waves. The SNOs calcium waves do not have specific sites of origin however they slowly propagate in a unidirectional manner, activating the entire network. Together, we propose that the tonic reduction of IM makes the neuronal network prone to the generation of seizures and the paroxysmal activity is generated when neurons are sufficiently depolarized, and reach the membrane potential where IM is normally activated. Our data indicate that this depolarization occurs due to activation of extrasynaptic NMDA receptors. In total our experiments reveal that mGluRs and NMDA receptors work in synergy playing an important role in the generation of seizures. We speculate that this synergy happens in neuronal pathologies associated with an imbalance in glutamate homeostasis such as anoxo-ischemic insults.